Gas-high viscosity oil flow in vertical large diameter pipes - Mohammed, Shara Kamal (2017)
Gas flow in columns of high viscosity liquids is found in heavy oil and bitumen production, polymer manufacturing and in Volcanology as silicate magmas in the volcanic conduit. Predicting the characteristics of the hydrodynamics of gas flow, under such conditions is essential in both design and safety assessments. In oil and gas industry, it is very important in the design of the equipment and the very long pipelines. Further, it is important in the design and safety of the industrial equipment and the pipelines in the polymer manufacturing. Finally, the ability to predict natural phenomenon and develop the knowledge about volcanoes activity and the nature of eruptions in volcanoes is important for the assessment of environmental risks. The majority of the works, which have studied gas-liquid flow in pipes, have been carried out mainly by using water or liquids of low viscosities (<1 Pa.s). Knowledge, regarding the hydrodynamics of gas flow in high viscosity liquids and large diameter columns, is still limited though despite the importance of this subject. In this work, the characteristics of gas-high viscosity oils in large diameter columns were studied over a wide range of gas flow rates. Two column geometries were used: one of 240 mm and the other of 290 mm internal diameter. The columns were initially filled with stagnant Silicone oil of viscosities 360 and 330 Pa.s respectively. Electrical Capacitance Tomography (ECT) technique was employed for the data measurements besides a high-resolution camera. In general, 4 flow patterns are found over the selected range of gas flow rates. These are seen to differ from the ones in lower viscosity liquids. First, bubbly flow consists of single spherical bubbles that rise at a constant velocity in the centre of the column at low gas flow rates. Second, slug flow which consists of long bubbles (Taylor bubble) with rounded top and end, with a diameter almost equal to the column diameter and separated by liquid slugs. The third flow pattern is the transition to churn flow which occurs due to further increase of gas flow rate. The falling film, around the very long bubbles, accumulates to create regions of high frequency activity that consists of liquid bridges. These regions are named “churn” regions. The length of this region increases gradually with increasing the gas flow rate. At very high gas flow rates, the gas flows through an open wavy non-symmetrical core in the column of the viscous oil (churn regions). The length of the churn regions increases significantly at this flow regime which can be named churn flow regime. Small bubbles of millimetres to centimetres diameter are seen to accumulate in the column due to the high viscosity and low velocity of the liquid motion. These bubbles generate due to the bubble eruption at the top section, bubble coalescence along the column and at the gas injection points at the bottom of the column.